The Mediating Role of Attitude in the Correlation between Creativity and Curiosity regarding the Performance of Outstanding Science Teachers - Ramdani, Z.; Hadiana, D.; Amri, A.; Warsihna, J.; Widodo, W.; Chandra, D. T.; Sopandi, E. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Significant and unexpected changes need to be anticipated by all teachers, especially when facing difficult situations in the learning process. This study aims to determine the mediating role of attitude in the correlation between creativity and curiosity regarding the performance of outstanding science teachers. A quantitative causal method was used which involves 100 teachers that were selected using a purposive sampling technique. Collection of research data using four questionnaire instruments with a Likert-scaled were derived from the existing grand theory and met the psychometric properties as a suitable instrument to use. Multiple regression analysis is used to identify the relationship between these variables. The results of the data analysis showed that the creativity affects attitude directly and attitude also affects performance. Other results show that curiosity has a direct effect on performance and has no indirect effect on performance. Meanwhile, other results also explained that the investigated variables are positively correlated with the outstanding science teachers. The results of the study concluded that attitude can act as an effective mediator in the relationship between creativity and performance. Creativity and curiosity are important variables to support the performance of outstanding science teachers. The limitations of this study and discussions were subsequently explained in this article.